THERAPEUTIC EFFECTS OF POMEGRANATE SEED OIL: EXPERIMENTAL EVIDENCE AND TRANSLATIONAL PROSPECTS (Journal of Universal Science Research, 2025)
Pomegranate seed oil (PSO) exhibits a multifaceted pharmacological profile attributable to its high concentration of punicic acid, tocopherols, and a diverse array of polyphenols. This critical review integrates current pre‑clinical findings with original data generated by the authors in a nitrous oxide–induced rat model of hepatic fibrosis. PSO administration (1 mL kg⁻¹ day⁻¹, 30 days) attenuated collagen deposition and down‑regulated key profibrotic mediators—TGFβ1, α-SMA, and CD68—by 40-45 % versus untreated fibrotic controls (p